Learning difficulties? - White, Harry (Strad, 2019)
The article discusses the crticism regarding the ABRSM, the UK's leading music examinations board, drafting a new model music curriculum for the Government including that the ABRSM which is an organisation that has never engaged with music education in the classroom was asked to undertake the work.